Postpartum Diagnosis of AML-M3: A Rare Case Report - Manjula Biradar; Praveen Biradar; Sharada M.S (Journal of Krishna Institute of Medical Sciences University)
A 27 year old female gravid 2, para 1, presented at 39 weeks of gestation with pain in abdomen going in for labour, and delivered healthy baby. The patient later had post-partum haemorrhage with Prothrombin Time (PT) 10min, platelet count 70,000 cells/cumm. Peripheral smear showed shift to left with myeloblasts, promyelocytes. The diagnosis of Acute Myeloid Leukemia (AML) was given and advised for bone marrow examination. The diagnosis AML-M3 was confirmed by marrow study. Unfortunately, patient went in for Disseminated Intravascular Coagulation (DIC) and died 2 days after the diagnosis.